2003
DOI: 10.1124/mol.64.3.587
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of RGS2 and RGS4 to the Plasma Membrane by G Proteins and Receptors Reflects Functional Interactions

Abstract: N-terminally green fluorescent protein (GFP)-tagged regulator of G protein signaling (RGS) 2 and RGS4 fusion proteins expressed in human embryonic kidney 293 cells localized to the nucleus and cytosol, respectively. They were selectively recruited to the plasma membrane by G proteins and correspondingly by receptors that activate those G proteins: GFP-RGS2 when coexpressed with G␣s, ␤ 2 -adrenergic receptor, G␣q, or AT 1A angiotensin II receptor, and GFP-RGS4 when coexpressed with G␣i2 or M 2 muscarinic recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 40 publications
6
83
1
4
Order By: Relevance
“…This has been reported for different RGS proteins in regulating Gq proteins activated by distinct receptors (Xu et al, 1999); RGS3 and muscarinic m3 receptor; RGS5 and angiotensin AT1a receptor (Wang et al, 2002); RGS8 towards muscarinic m1 and substance P receptors (Saitoh et al, 2002); RGS-R4 subfamily and subtypes of muscarinic acetylcholine receptors (Roy et al, 2003;Bernstein et al, 2004). In the present study, we show that both RGSZ1 and RGSZ2 co-precipitate with m-opioid receptors, and that the association between RGSZ and Ga subunits is altered by a morphine challenge.…”
Section: Discussionmentioning
confidence: 56%
“…This has been reported for different RGS proteins in regulating Gq proteins activated by distinct receptors (Xu et al, 1999); RGS3 and muscarinic m3 receptor; RGS5 and angiotensin AT1a receptor (Wang et al, 2002); RGS8 towards muscarinic m1 and substance P receptors (Saitoh et al, 2002); RGS-R4 subfamily and subtypes of muscarinic acetylcholine receptors (Roy et al, 2003;Bernstein et al, 2004). In the present study, we show that both RGSZ1 and RGSZ2 co-precipitate with m-opioid receptors, and that the association between RGSZ and Ga subunits is altered by a morphine challenge.…”
Section: Discussionmentioning
confidence: 56%
“…These proteins accelerate the exchange of GTP for GDP on the G-protein a subunit, thereby turning off the G-protein. Although nothing is known about RGS proteins in oocytes, it is interesting to note that RGS2 can inhibit G s -mediated cAMP production (Sinnarajah et al 2001, Kehrl & Sinnarajah 2002, Roy et al 2003. Thus, an RGS protein could potentially inhibit cAMP production in the oocyte following LH stimulation.…”
Section: How Does Lh Trigger Meiotic Resumption?mentioning
confidence: 99%
“…The mechanism whereby chronic olanzapine causes a redistribution of RGS4 protein is not clear but could be due to the increased expression of G αq /11 protein and 5-HT 2A receptor protein. A previous study demonstrated that localization of RGS protein to the membrane increases with increased expression of G α protein (Roy et al, 2003). However, in the cell culture system used in that study, G αi protein but not G αq protein expression increased association of RGS4 with the cell membrane.…”
Section: Discussionmentioning
confidence: 56%